Anti-Inflammatory and Anti-Arthritic Potential of Standardized Extract of Clerodendrum serratum (L.) Moon - Tiwari, Raj Kumar; Chanda, Silpi; M, Udayabanu; Singh, Manisha; Agarwal, Shriya (Frontiers in Pharmacology, 2021)
Aims: Scientific biological evaluation of standardized extracts is becoming one of the central needs for the globalization of customary medication in current times. And to validate the presence of active constituents in crude medicinal extracts, analytical techniques like HPLC and HPTLC are the most suitable authentication systems. In the current study we aimed to standardize and evaluate Clerodendrum serratum (L.) Moon (Verbenaceae). For its unique anti-inflammatory and anti-arthritic properties. Evaluation and analysis of the plant, therefore, offers a new platform for the development of the herbal drug and could prove to be a safe and cost effective treatment for arthritis management. Methods: The aqueous extract of C. serratum, a common plant in the Southeastern Asian region, was used for phytochemical investigation and standardization by HPTLC and HPLC. The standardized HPLC method was further validated by using ICH guidelines. The standardized extract was investigated for anti-inflammatory and anti-arthritic activity. Complete Freund’s adjuvant (CFA) model was performed to evaluate the activity. Paw diameter, joint diameter, arthritic score, and body weight was accepted as a parameter for the evaluation of biological activity. Results: HPTLC method revealed the presence of ursolic acid with an Rf value of 0.38 and the amount quantified was 0.03% w/w. The presence of the bioactive phytochemical was further analyzed and confirmed by HPLC for which the validation was done successfully in accordance with ICH guidelines. The assay content for ursolic acid was found to be 0.059% with relative standard deviation (RSD) <2.5% for specificity and precision with spike recovery between 95–110%. The anti-arthritic activity of aqueous extract exhibited COX-2 and TNF-α inhibition as observed in various parameters like paw edema, arthritic index, and joint diameter. Plant extract showed reclamation of arthritis in regard to body weight, arthritic score, paw edema, and joint diameter. The extract showed significant results for TNF-α and COX-2(p < 0.0001). The plant extract also exhibited in-vitro anti-inflammatory activity. Conclusion: The current study established the scientific basis of ethnomedicinal use of the plant for anti-inflammatory purposes and the management of arthritis and can also be used for quality control purposes.